2010
DOI: 10.1021/nl1036098
|View full text |Cite
|
Sign up to set email alerts
|

CdSe Quantum Dots for Two-Photon Fluorescence Thermal Imaging

Abstract: The technological development of quantum dots has ushered in a new era in fluorescence bioimaging, which was propelled with the advent of novel multiphoton fluorescence microscopes. Here, the potential use of CdSe quantum dots has been evaluated as fluorescent nanothermometers for two-photon fluorescence microscopy. In addition to the enhancement in spatial resolution inherent to any multiphoton excitation processes, two-photon (near-infrared) excitation leads to a temperature sensitivity of the emission inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
181
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 295 publications
(202 citation statements)
references
References 44 publications
4
181
2
1
Order By: Relevance
“…Luminescent thermometers based on temperature-dependent emission intensity and/or lifetime of dye-sensitized Pdots, 29,30 semiconducting QDs, 8,[31][32][33][34][35] and Ln…”
Section: Examples Of Such Miniaturization Encompassmentioning
confidence: 99%
See 1 more Smart Citation
“…Luminescent thermometers based on temperature-dependent emission intensity and/or lifetime of dye-sensitized Pdots, 29,30 semiconducting QDs, 8,[31][32][33][34][35] and Ln…”
Section: Examples Of Such Miniaturization Encompassmentioning
confidence: 99%
“…The technique of two-photon fluorescent microscopy has been recently developed using femtosecond lasers and it has been shown that QDs present a large NIR two-photon excitation cross-section. Maestro et al 35,109,177 demonstrated the potential use of CdSe and CdTe QDs as thermal mapping probes, as the emission peak and intensity depend on the environment temperature and can be imaged by means of a high-resolution two-photon fluorescence microscope. The authors performed studies with QDs in phosphate buffered saline solutions and in HeLa cervical cancer cells.…”
mentioning
confidence: 99%
“…2(a)). 14 The mixed solution was placed within a microscope slide containing a 200 lm height and 2 mm width l-channel (provided by Ibidi Inc.). The microscope slide was placed in a doublebeam microscope as it is schematically shown in Fig.…”
Section: à3mentioning
confidence: 99%
“…8 In addition, recent works have demonstrated the ability of QDs to act as nano-thermometers based on the thermal sensitivity of their fluorescence bands. [9][10][11][12][13][14] Based on all these outstanding properties, QDs have been successfully used to mark specific receptors in cell membranes, to measure intracellular temperature, and to label living embryos at different stages. 9,[15][16][17] Most of the QD-based bio-images reported up to now were obtained by using either CdSe or CdTe QDs, since both are currently commercially available with a high degree of quality.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Based on all these outstanding properties, QDs have been successfully used to mark specific receptors in cell membranes, to measure intracellular temperature, and to label living embryos at different stages. 9,[15][16][17] Most of the QD-based bio-images reported up to now were obtained by using either CdSe or CdTe QDs, since both are currently commercially available with a high degree of quality. 7,[18][19][20] Although they show similar fluorescence properties and optical performance, CdTe QDs have very recently attracted much attention, since a hyper-thermal sensitivity of their fluorescence bands was discovered.…”
Section: Introductionmentioning
confidence: 99%